Glorifikasi Instrumen Biola sebagai Sarana untuk Mengembangkan Genre Heavy Metal pada Band Musik Resolution15 - Fadly, Muhammad (Urban: Jurnal Seni Urban, 2019)
A genre or an approach in art is an identity for the art. It is not just itself in an empty space, but it was born and developed in an established system. Likewise, the genre in music; in general stable and orderly systems are ‘broken’ to form new genres. This product of musical violation produces an innovation, and evolves by being characterized by a constant flow of new violations, mainly due to the support of technological advances. In addition to technology, the personality of the musicians also contributes significantly; they add certain characteristics that are unique and distinctive to a band. This research is a study of the glorification process on violins by Earl Maneein in the metal core music band, Resolution15; glorification is a new technique and serves as the instrumentation media in the heavy metal music genre, and metal core is a further development of the genre. This study aims to analyze the creation of new genres through violin glorification in the bigger genre of heavy metal music. As a case study with historical and musicological approaches, this research shows that the glorification of instruments can be a new part of the classification of the formation of genre.Sebuah aliran atau genre di dalam seni adalah sebuah identitas bagi sebuah seni. Tidak berada di dalam ruang hampa, genre lahir dan berkembang di dalam sebuah sistem yang mapan. Demikian juga dengan genre musik; pada umumnya sistem yang stabil dan teratur ‘dilanggar’ untuk membentuk genre baru. Produk pelanggaran ini menghasilkan sebuah inovasi, dan berevolusi dengan ditandai oleh aliran pelanggaran baru yang konstan, terutama karena dukungan kemajuan teknologi. Selain teknologi, pribadi musisi juga berkontribusi secara signifikan; ia memberikan ciri tertentu yang unik dan khas pada sebuah band. Penelitian ini merupakan kajian tentang proses glorifikasi pada biola yang dilakukan Earl Maneein di dalam band musik metalcore, yaitu Resolution15; glorifikasi itu berupa teknik serta media instrumentasi baru di dalam genre musik heavy metal, dan metalcore merupakan perkembangan lebih lanjut dari genre tersebut. Penelitian ini bertujuan menganalisis penciptaan genre baru melalui glorifikasi biola di dalam genre besar musik heavy metal. Sebagai studi kasus dengan pendekatan sejarah dan musikologi, penelitian ini menunjukkan bahwa glorifikasi instrumen dapat menjadi bagian baru untuk mengklasifikasikan terbentuknya genre.